(untitled) (World Bulletin of Social Sciences, 2024)
In recent years, many researchers have been carried out on the sociopolitical activity of young people, their participation in the activities of government bodies, their place in education, culture and other areas. In this article is analyzed the forms of youth participation in the decisionmaking process on issues relating to themselves and the local community, the principles of youth participation in Uzbekistan and the direction of youth participation.